Polarization of state financial control on the basis of the subject matter of the subjects control - Kurianov , V. V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
This article considers mechanism of financial control over public resources of Ukraine based on agents of the institute of control: the Accounting Chamber of Ukraine, the State Audit Service of Ukraine, the State Treasure Service of Ukraine and structural units of internal audit. The notions: “agent of institute of control”, “supreme financial control” and “supreme financial control body”, have been considered. Also there are considered the structure of public resources and control over its structural parts, is determined the notion “the subject of control”.  Competencies of agents of the institute of control who control  public resources and actions have been determined. The analysis of the effectiveness of subjects of control over public resources has been done. The need to optimize the competencies of agents of institute of control and their interactions has been determined. It has been pointed that in Ukraine there is no separation of types of control: internal, external and supreme. The need in supreme financial control body in the system of state financial control of Ukraine has been determined. Also there is considered  hierarchy of types of control, and there has been stated the author’s vision of their polarization, that will change the system of state financial control of the state. The formulated system is based on international standards ISSAI, which define how the supreme financial control body and its competencies should function. This polarization of types of control optimize the mechanism of financial control, which ensures the development of society, the accumulation and saving public finances, the provision of public goods and social and economic growth of the state.